Conductive paste composition, its application, crystalline silicon solar cell electrode and its manufacturing method

The use of lead-boron-selenium or bismuth-boron-selenium glass frits in conductive pastes for solar cells addresses the issues of high resistance and toxicity in conventional pastes, improving efficiency and environmental safety by forming low-resistance electrical connections with p-type semiconductors.

JP7607250B2Active Publication Date: 2024-12-27SOLAMET ELECTRONIC MATERIALS (DONGGUAN) CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022552788
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-20
Filing Date
2022-03-10
Publication Date
2024-12-27
Estimated Expiration
2042-03-10

AI Technical Summary

Technical Problem

Conventional conductive metal pastes for crystalline silicon solar cells face challenges in achieving low electrical contact resistance and carrier recombination due to the high glass transition temperature of lead-boron-silicon glass frits, which hinder efficient photovoltaic conversion, and the use of toxic elements like thallium poses environmental and health risks.

Method used

A conductive paste composition using lead-boron-selenium glass frit or bismuth-boron-selenium glass frit, with a lower glass transition temperature, that does not contain toxic elements, allowing for controlled etching of passivation films to form low-resistance electrical connections with p-type semiconductors, thereby improving photovoltaic efficiency and reducing environmental impact.

Benefits of technology

The proposed paste compositions achieve low electrical resistance and reduced carrier recombination, enhancing the photovoltaic conversion efficiency of solar cells while being safer for the environment and easier to recycle, without the use of harmful substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607250000006
    Figure 0007607250000006
  • Figure 0007607250000007
    Figure 0007607250000007
  • Figure 0007607250000008
    Figure 0007607250000008
Patent Text Reader

Abstract

A conductive paste composition, its manufacturing method, applications, and a crystalline silicon solar cell are disclosed. The conductive paste composition contains silver powder and aluminum powder, and also contains lead-boron-selenium glass frit or bismuth-boron-selenium glass frit. The conductive paste composition can perform good etching of the passivation film of an n-type crystalline silicon solar cell during high-temperature sintering, but does not excessively oxidize the aluminum powder contained therein, and can form an electrode having good electrical contact with a p-type doped emitter.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] (CROSS REFERENCE TO RELATED APPLICATIONS) This application claims priority to Chinese Patent Application No. 202111558682.4, entitled "Conductive paste composition, its manufacturing method, application and crystalline silicon solar cell," filed with the State Intellectual Property Administration of China on December 20, 2021, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to the technical field of photovoltaic devices, in particular to a conductive paste composition, its manufacturing method, applications and crystalline silicon solar cells. [Background technology]

[0003] Solar cells are used to convert solar energy into direct current energy, and their basic structure has a pn junction formed by a p-type semiconductor and an n-type semiconductor. More specifically, an n-type crystalline silicon solar cell, which is one type of solar cell, uses an n-type doped silicon wafer (e.g., a phosphorus-doped silicon wafer) as a substrate, and forms a p-type doped semiconductor on its surface by a doping method (e.g., using boron doping), thereby forming a pn junction. The p-type doped semiconductor is also called a p-type emitter. At least one layer of a passivation film, such as Al2O3 or SiN, is formed on the surface of the p-type emitter. x etc. are deposited. The passivation film serves the effects of passivation and anti-reflection, maximizing the photoelectric conversion efficiency of the solar cell. It is then metallized to form an electrode in the form of a conductive metal contact with the p-type emitter, so that the current generated by photoelectric conversion can be conducted to an external circuit load.

[0004] When manufacturing a crystalline silicon solar cell, the front and back surfaces of the battery cell need to be metallized. In metallizing the front (light-receiving surface) of the battery cell, a conductive metal paste is generally printed on the surface of the passivation film in a desired pattern using a screen printing method, and then the conductive metal paste is etched through the passivation film by high-temperature sintering to make electrical contact with the emitter, thereby forming a conductive structure (also called an electrode) that exists in the form of a conductive metal contact. The electrical contact quality of the electrode includes the electrical contact resistance and carrier recombination due to metallization, which directly affect the photoelectric conversion efficiency of the solar cell. Generally, the conductive metal paste for forming the electrode includes a conductive material (e.g., silver particles), a glass frit, and an organic medium that functions as a printing vehicle. In order to achieve a low-resistance ohmic contact, aluminum powder may be further added to the conductive metal paste for contacting the p-type semiconductor.

[0005] In order to ensure good electrical contact between the conductive metal paste and the p-type semiconductor and to balance the carrier recombination, the conductive metal paste needs to control the etching degree of the passivation film to a reasonable level during high-temperature sintering. If the etching degree is insufficient, the conductive metal paste cannot penetrate the passivation film, and therefore the conductive metal paste cannot make ohmic contact with the p-type semiconductor. If the etching degree is too large, the excessive etching will greatly increase the carrier recombination, resulting in a loss of the open circuit voltage of the cell, and further affecting the photoelectric conversion efficiency.

[0006] As one of the important components of the conductive metal paste, the glass frit mainly functions to etch the passivation film, so the components of the glass frit also directly affect the conversion efficiency of the metallized crystalline silicon solar cell.

[0007] At present, the glass frit of the conductive metal paste in contact with the p-type semiconductor is generally a lead-boron-silicon glass frit containing lead oxide, boron oxide and silicon oxide. The lead-boron-silicon glass frit has a high glass transition temperature (Tg point), which is disadvantageous for high-temperature rapid firing of crystalline silicon solar cells. To lower the Tg point of the lead-boron-silicon glass frit, common methods include reducing the content of boron element with a high melting point, increasing the content of elements with flux (e.g., alkali metals, alkaline earth metals or rare earth metals), or adding thallium element (Tl). However, if the content of boron element is too low, the glass frit is difficult to maintain an amorphous state and is prone to crystallization. And if the content of alkali metals, alkaline earth metals or rare earth metals is too high, the Tg point can be lowered, but due to their high corrosion performance, it affects the efficiency of the photovoltaic device. Also, although thallium element can effectively lower the Tg point, it is a highly toxic element, harmful to the human body, and pollutes the environment. Therefore, it is necessary to find a glass former that can effectively lower the Tg for conductive paste (or called conductive agent) containing aluminum powder for contacting p-type semiconductors. For example, for p-Type crystalline silicon cell technology, such as Passivated emitter and rear cell (p-PERC) or Passivated emitter and rear cell-selective emitter (p-PERC-SE), tellurium element has already been proven to be a very effective glass former, but tellurium oxide can oxidize aluminum powder in the conductive metal paste for contacting p-type semiconductors, thus affecting the ohmic contact and reducing the efficiency of the photovoltaic device. Summary of the Invention [Problem to be solved by the invention]

[0008] In order to overcome the above-mentioned deficiencies, some embodiments of the present application provide a conductive paste composition capable of making electrical contact with a p-type doped semiconductor (hereinafter, abbreviated as p-type semiconductor) of an n-type crystalline silicon solar cell during a sintering process, a manufacturing method thereof, applications thereof, and a crystalline silicon solar cell electrode, or an n-type crystalline silicon solar cell. [Means for solving the problem]

[0009] Some embodiments of the present application use the following technical solutions.

[0010] [Type 1 conductive paste, its manufacturing method and applications] According to some embodiments of the present application, there is provided a first conductive paste composition for making an electrical connection with a p-type semiconductor of an n-type crystalline silicon solar cell.

[0011] The first conductive paste composition comprises: (1) a lead-boron-selenium glass frit that accounts for 0.5% to 10% (weight percentage) of the total solid content of the conductive paste composition; (2) a conductive component that accounts for 87% to 99% (weight percentage) of the total solid matter of the conductive paste composition; (3) an aluminum component that accounts for 0.5% to 3% (weight percentage) of the total solid content of the conductive paste composition; (4) An organic medium.

[0012] The lead-boron-selenium glass frit, the conductive component, and the aluminum component are the total solids of the conductive paste composition, and the sum of the weight percentages of the three is 100%, but since the organic medium is thermally decomposed in the subsequent processing steps, the content of the organic solvent is calculated separately and is not included in the above 100%. The lead-boron-selenium glass frit is a solid based on lead-boron-selenium-oxide, and is at least used to make an electrical connection with a p-type semiconductor by etching a passivation film in an n-type crystalline silicon solar cell. The conductive component forms a silver-aluminum electrode for electrical connection with a p-type semiconductor after sintering. The organic medium is used to disperse the solids and provide printing performance.

[0013] In some embodiments, the conductive paste compositions and lead-boron-selenium glass frits of the present application do not contain any form of elemental tellurium (Te), such as TeO2.

[0014] In other embodiments, the lead-boron-selenium glass frit contains no more than 1.2 wt. % TeO2, calculated based on the total dry weight of the lead-boron-selenium glass frit.

[0015] In some embodiments, the lead-boron-selenium glass frit contains at least 50%-85% PbO, 2%-34% B2O3, and 0.1%-16% SeO2, calculated based on the total dry weight of the lead-boron-selenium glass frit, the percentages being by weight (wt%).

[0016] In some other embodiments, the lead-boron-selenium glass frit may further contain 0.1% to 25% of additives, calculated based on the total weight of the dry weight of the lead-boron-selenium glass frit. The additives are any one or more selected from the group consisting of PbF2, SiO2, Bi2O3, BiF3, AgO2, Ag2O, AgO, ZnO, MgO, CaO, Al2O3, Li2O, Na2O, K2O, Rb2O, Ce2O, and Fe2O3. If the lead-boron-selenium glass frit does not contain additives, it is necessary to ensure that the sum of the total contents of the three components PbO, B2O3, and SeO2 in the dry weight of the lead-boron-selenium glass frit is 100%. When the lead-boron-selenium glass frit contains additives, it is necessary to ensure that the sum of the total contents of PbO, B2O3, SeO2 and additives is 100%. On the premise that the sum of the total contents of each component in the lead-boron-selenium glass frit is 100%, the content of each component can be adjusted to any value within the above range. This also applies to the adjustment of the content of each component in the bismuth-boron-selenium glass frit.

[0017] In some embodiments, the content of PbO in the lead-boron-selenium glass frit may be 51.0%-82.0%, 55%-75%, 65.9%-74.5%, 68.8%-73.1%, or 70%-71.7%, calculated based on the total weight (wt%) of the dry weight of the lead-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the weight contents of each component in the lead-boron-selenium glass frit is 100%.

[0018] In some embodiments, the content of B2O3 in the lead-boron-selenium glass frit may be 3%-32%, 4%-30%, 2%-20%, 6.8%-10%, 7.1%-7.6%, or 7.4%-7.5%, calculated based on the total dry weight of the lead-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the contents of each component in the lead-boron-selenium glass frit is 100%.

[0019] In some embodiments, the content of SeO2 in the lead-boron-selenium glass frit may be 0.2%-15%, 0.5%-13.1%, 1%-10%, 1.9%-9.4%, 2.1%-8.1%, or 3.7%-5.6%, calculated based on the total dry weight of the lead-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the contents of each component in the lead-boron-selenium glass frit is 100%.

[0020] In some embodiments, the content of the additive in the lead-boron-selenium glass frit may be 0.5% to 20%, 5% to 19%, 8% to 17%, 10% to 16%, 14.2% to 15.7%, or 14.7% to 15.3%, calculated based on the total weight of the dry weight of the lead-boron-selenium glass frit.

[0021] In some embodiments, the lead-boron-selenium oxide in the lead-boron-selenium glass frit is in a completely amorphous state when in the molten state during sintering.

[0022] In some other embodiments, the lead-boron-selenium oxide in the lead-boron-selenium glass frit is partially amorphous and partially crystalline when in a molten state, and the content of the crystalline portion of the lead-boron-selenium oxide in the lead-boron-selenium glass frit is 1.5% or less of the total weight of the lead-boron-selenium oxide.

[0023] In some embodiments, the conductive component may be one or more mixtures selected from elemental silver (e.g., silver powder), silver alloys, silver salts, or silver derivatives, and may, of course, contain other metals such as copper, palladium, or derivatives of these metals.

[0024] In some other embodiments, the weight percentage of the conductive component based on the total solid matter of the conductive paste composition may be 87% to 99%, 88% to 98%, 90% to 97%, 91% to 96%, 92% to 95%, or even 93% to 94%.

[0025] In some embodiments, the conductive paste composition contains 100 ppm or less of Cd and / or Tl. Since Cd and / or Tl have a certain toxicity, and if the paste contains excessive toxic substances, it is harmful to the environment, it is preferable that the conductive paste composition does not contain Cd and / or Tl.

[0026] The first conductive paste composition according to some embodiments of the present application can be used to manufacture photovoltaic devices such as n-type crystalline silicon solar cells, in which the conductive paste composition forms a conductive structure that penetrates the passivation film of the n-type crystalline silicon solar cell and makes electrical contact with the p-type semiconductor.

[0027] According to some embodiments of the present application, (1) providing a semiconductor substrate having an n-type crystalline silicon substrate (also referred to as an n-type lightly doped substrate), a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and a passivation film deposited on the surface of the p-type doped emitter; (2) applying the conductive paste composition to at least a portion of a surface of a passivation film on a surface of a p-type doped emitter; and (3) sintering the semiconductor substrate and the conductive paste composition applied to the semiconductor substrate, such that the conductive paste composition etches through the passivation film during the sintering process to form a conductive structure (also called an electrode) that makes electrical connection with the p-type doped emitter, thereby obtaining an n-type crystalline silicon solar cell electrode. The n-type crystalline silicon solar cell electrode is one component of the n-type crystalline silicon solar cell.

[0028] The numbers of the above steps do not limit the order of the steps.

[0029] In step (1), in some embodiments, the n-type crystalline silicon substrate is doped with a phosphorus source on the backside of the silicon wafer, followed by doping diffusion to form a high concentration of N + A region is formed, called the n-type back surface field (BSF), where phosphorus acts as a diffusion medium, and a p-type semiconductor is the portion of the crystalline silicon wafer that is front-side p-doped (e.g., boron), called the p-type emitter, which forms a p-n junction with the n-type crystalline silicon substrate. The front side is defined as the surface of the n-type crystalline silicon solar cell that receives sunlight (also called the light-receiving surface), and the back side is defined as the surface of the n-type crystalline silicon solar cell that does not receive sunlight (also called the non-light-receiving surface).

[0030] In step (2), in some embodiments, the conductive paste composition is applied in the form of a pattern onto at least a portion of the surface of the passivation film on the surface of the p-type semiconductor.

[0031] According to some embodiments of the present application, A semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and at least one layer of a passivation film deposited on a surface of the p-type doped emitter; and a conductive structure formed from the conductive paste composition, the conductive structure penetrating at least a portion of the passivation film and in electrical contact with the p-type doped emitter.

[0032] According to some embodiments of the present application, there is further provided an n-type crystalline silicon solar cell including the n-type crystalline silicon solar cell electrode. In some embodiments, the n-type crystalline silicon solar cell may be a photovoltaic device such as an n-PERT solar cell or an n-TOPCon solar cell.

[0033] [Type 2 conductive paste, its manufacturing method and applications] According to some embodiments of the present application, there is further provided a second conductive paste composition for electrically connecting with a p-type semiconductor of an n-type crystalline silicon solar cell. The same contents of the first conductive paste composition as those of the second conductive paste composition of this part are incorporated herein by reference, and the description thereof will be omitted. Compared with the first conductive paste composition, the conductive paste composition of this part does not contain highly toxic elements such as lead, cadmium, and thallium, so that it does not cause serious harm to the human body or the environment and is easy to recycle. In addition, the second conductive paste composition of this part and its glass frit do not contain any form of tellurium element (Te), such as tellurium oxide (TeO2).

[0034] Specifically, the second type of conductive paste composition of this part is (1) a bismuth-boron-selenium glass frit that accounts for 0.5% to 10% (weight percentage) of the total solid content of the conductive paste composition; (2) a conductive component that accounts for 87% to 99% (weight percentage) of the total solid matter of the conductive paste composition; (3) an aluminum component that accounts for 0.5% to 3% (weight percentage) of the total solid content of the conductive paste composition; (4) An organic medium.

[0035] The bismuth-boron-selenium glass frit, the conductive component, and the aluminum simple component constitute the total solid matter of the conductive paste composition, and the sum of the weight percentages of the three in the total solid matter of the conductive paste composition is 100%.

[0036] In some embodiments, the bismuth-boron-selenium glass frit contains at least 50% to 90% Bi2O3, 2% to 35% B2O3, and 0.1% to 15% SeO2, calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit. Meanwhile, in other embodiments, the bismuth-boron-selenium glass frit may further contain 0.1% to 25% of an additive, the additive being any one or more selected from the group consisting of SiO2, BiF3, AgO2, Ag2O, AgO, ZnO, MgO, CaO, Al2O3, Li2O, Na2O, K2O, Rb2O, Ce2O, and Fe2O3, calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit. The additive does not contain oxides or halides of highly toxic elements.

[0037] In some embodiments, when calculated based on the dry weight (total weight) of the bismuth-boron-selenium glass frit, the content of Bi2O3 in the lead-boron-selenium glass frit may be 52% to 90%, 55% to 88%, 58% to 85%, 60% to 80%, 66.6% to 75%, 68.9% to 71.3%, or even 70% to 71%.

[0038] In some embodiments, the content of B2O3 in the bismuth-boron-selenium glass frit may be 2% to 20%, 3% to 18%, 5% to 16%, 7% to 15%, 10.5% to 12%, 10.9% to 11.6%, or 11.1% to 11.3%, calculated based on the dry weight of the bismuth-boron-selenium glass frit.

[0039] In some embodiments, the content of SeO2 in the bismuth-boron-selenium glass frit may be 0.1% to 15%, 0.2% to 14%, 1% to 13%, 2% to 12.4%, 3.1% to 9.3%, or even 3.5% to 6.2%, calculated based on the dry weight of the bismuth-boron-selenium glass frit. The adjustment of the content of each of the above components is required to ensure that the sum of the contents of each component in the bismuth-boron-selenium glass frit is 100%.

[0040] In some embodiments, the bismuth-boron-selenium glass frit further contains 0.1% to 5% Li2O, calculated based on the dry weight (total weight) of the bismuth-boron-selenium glass frit.

[0041] In some embodiments, the bismuth-boron-selenium glass frit further contains 0.1% to 5% Na2O, calculated based on the dry weight (total weight) of the bismuth-boron-selenium glass frit.

[0042] In some embodiments, the bismuth-boron-selenium glass frit further contains 0.1% to 20% ZnO, calculated based on the dry weight (total weight) of the bismuth-boron-selenium glass frit.

[0043] In some embodiments, the conductive component is one or more mixtures selected from elemental silver (eg, silver powder), silver alloys, and silver salts.

[0044] In some embodiments, the bismuth-boron-selenium oxide in the bismuth-boron-selenium glass frit is in a completely amorphous state when in the molten state during sintering.

[0045] In some other embodiments, the bismuth-boron-selenium oxide in the bismuth-boron-selenium glass frit is partially amorphous and partially crystalline when in a molten state, and the content of the crystalline portion of the bismuth-boron-selenium oxide in the bismuth-boron-selenium glass frit is 1.5% or less of the total weight of the bismuth-boron-selenium oxide.

[0046] According to some embodiments of the present application, there is further provided an application of the conductive paste composition in an n-type crystalline silicon solar cell, in which the conductive paste composition etches through a passivation film of the n-type crystalline silicon solar cell to form a conductive structure that makes an electrical connection with a p-type doped emitter of the n-type crystalline silicon solar cell.

[0047] According to some embodiments of the present application, (1) providing a semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and at least one passivation film deposited on the surface of the p-type doped emitter; (2) applying the conductive paste composition to at least a portion of a surface of a passivation film; and (3) sintering the semiconductor substrate and the conductive paste composition applied to the semiconductor substrate, such that the conductive paste composition etches through the passivation film during the sintering process to form a conductive structure (also called a silver-aluminum electrode) that makes electrical connection with the p-type doped emitter, thereby obtaining an n-type crystalline silicon solar cell electrode.

[0048] In step (1), in some embodiments, the n-type crystalline silicon substrate is doped with a phosphorus source by doping the backside of the silicon wafer with a high concentration of N. + A region is formed, called an n-type back surface field (BSF), where phosphorus acts as a doped diffusion medium, and a p-type semiconductor is formed, called a p-type emitter, where a silicon wafer portion is front-side p-type doped (e.g., boron), which forms a p-n junction with the n-type crystalline silicon substrate.

[0049] In some embodiments, the second conductive paste composition is applied to at least a portion of the surface of the passivation film in the form of a pattern.

[0050] According to some embodiments of the present application, A semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and at least one layer of a passivation film deposited on a surface of the p-type doped emitter; and a conductive structure formed from the conductive paste composition, the conductive structure penetrating at least a portion of the passivation film and making electrical connection with the p-type doped emitter.

[0051] According to some embodiments of the present application, there is further provided an n-type crystalline silicon solar cell including the above n-type crystalline silicon solar cell electrode.

[0052] In some embodiments, the n-type crystalline silicon solar cell may be a photovoltaic device such as an n-PERT solar cell or an n-TOPCon solar cell. Effect of the Invention

[0053] By using the above technical means, some embodiments of the present application achieve the following technical effects.

[0054] First, the conductive paste composition in some examples of the present application contains a glass frit having a desired low Tg point, but does not contain an oxide component that excessively oxidizes the aluminum element in the silver-aluminum paste. Therefore, the passivation film of the photovoltaic device can be etched at a controllable rate, and in the sintering process after etching, the silver-aluminum paste can penetrate the passivation film of the photovoltaic device and form a silver-aluminum electrode that makes good electrical contact with the p-type semiconductor. Therefore, the manufactured photovoltaic device has a good fill factor (FF) and photoelectric conversion efficiency (η).

[0055] Secondly, since the conductive paste composition in some embodiments of the present application does not contain highly toxic elements such as cadmium and thallium, the manufactured photovoltaic device has low toxicity, helps to reduce harm to the human body and the environment, and is easy to recycle. [Brief description of the drawings]

[0056] In order to more clearly describe the technical solutions in the embodiments of the present application, the drawings in the embodiments are briefly described below. The drawings in the following description are only some embodiments of the present application, and it is obvious that those skilled in the art can also obtain other drawings based on these drawings without creative efforts.

[0057] [Figure 1] A cross-sectional view of an n-type solar cell manufactured by applying a conductive paste composition in some embodiments of the present application. Fig. 1 shows only the case where a first conductive paste composition is used. In practice, the conductive paste composition may be the first conductive paste composition (containing lead-boron-selenium glass frit) or the second conductive paste composition (containing bismuth-boron-selenium glass frit). [Diagram 2]FIG. 2 is a cross-sectional view of an n-type tunnel oxide passivated contact (abbreviated as n-TOPCon) solar cell manufactured by applying a conductive paste composition in some embodiments of the present application. FIG. 2 shows only the case where a first conductive paste composition is used. In practice, the conductive paste composition may be the first conductive paste composition (containing lead-boron-selenium glass frit) or the second conductive paste composition (containing bismuth-boron-selenium glass frit). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0058] The technical solutions of the present application will be described below clearly and completely, but it is clear that the embodiments described herein are only some of the embodiments of the present application, and are not all of the embodiments. Based on the embodiments in the present application, all other embodiments that a person skilled in the art can obtain without any creative effort fall within the scope of protection of the present application.

[0059] The present application provides a conductive paste composition, its manufacturing method and application. The conductive paste composition may be called a thick film paste composition, and includes a first conductive paste composition (containing lead-boron-selenium glass frit) and a second conductive paste composition (containing bismuth-boron-selenium glass frit). Each of them will be described in detail below. Note that the order of description of the following examples does not limit the preferred order of the examples.

[0060] [First type of conductive paste composition] Some embodiments of the present application provide a first conductive paste composition for making a low resistance electrical connection with a P-type semiconductor in a photovoltaic device.

[0061] A first conductive paste composition according to some embodiments of the present application comprises: (1) a lead-boron-selenium glass frit; (2) a conductive component; (3) an aluminum component; (4) An organic medium.

[0062] The lead-boron-selenium glass frit, the conductive component and the aluminum simple component are solid components of the conductive paste composition, and the sum of the weight percentages of the solid components of the conductive paste composition is 100%. The organic medium is a dispersed phase in the conductive paste composition and provides printing performance.

[0063] Each component will be described individually below.

[0064] Lead-boron-selenium glass frit In some embodiments, the lead-boron-selenium glass frit is a composition having a glass component, and may account for 0.5% to 10% of the total solid matter of the conductive paste composition. In some other embodiments, the ratio of the lead-boron-selenium glass frit to the total solid matter of the conductive paste composition may be 0.8% to 9.8%, 1% to 9.5%, 1.5% to 9%, 2% to 8%, 3% to 7%, 4% to 6%, or 5% to 5.5%. The percentage of each component in the conductive paste composition is expressed as a weight percentage (wt%), and the same applies below. The ratio of the lead-boron-selenium glass frit to the total solid matter of the conductive paste composition needs to be adjusted to ensure that the sum of the weight percentages of each component in the conductive paste composition is 100%.

[0065] In some embodiments, the lead-boron-selenium glass frit contains at least 50%-85% PbO, 2%-34% B2O3, and 0.1%-16% SeO2. The percentage of each component in the glass frit is expressed by weight (wt%), and is calculated based on the total dry weight of the lead-boron-selenium glass frit. The proportion of each component in the lead-boron-selenium glass frit must be adjusted to ensure that the sum of the proportions of each component in the total dry weight of the lead-boron-selenium glass frit is 100%.

[0066] In some embodiments, the content (wt%) of PbO in the lead-boron-selenium glass frit may be 51.0%-82.0%, 55%-75%, 65.9%-74.5%, 68.8%-73.1%, or 70%-71.7%, calculated based on the total dry weight of the lead-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the contents of each component in the lead-boron-selenium glass frit is 100wt%.

[0067] In some embodiments, the content of B2O3 in the lead-boron-selenium glass frit may be 3%-32%, 4%-30%, 2%-20%, 6.8%-10%, 7.1%-7.6%, or 7.4%-7.5%, calculated based on the total dry weight of the lead-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the contents of each component in the lead-boron-selenium glass frit is 100wt%.

[0068] In some embodiments, the content of SeO2 in the lead-boron-selenium glass frit may be 0.2%-15%, 0.5%-13.1%, 1%-10%, 1.9%-9.4%, 2.1%-8.1%, or 3.7%-5.6%, calculated based on the total dry weight of the lead-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the contents of each component in the lead-boron-selenium glass frit is 100 wt%.

[0069] In some embodiments, in addition to the above three basic components, the lead-boron-selenium glass frit may further contain additives. The naming of the lead-boron-selenium glass frit in each embodiment of the present application does not mean that the glass frit contains only three elements, lead, boron, and selenium, but it may contain other components, such as other elements or additives. These three elements belong to the basic components of the glass frit and are easy to distinguish from the bismuth-boron-selenium glass frit, so they are named as above in this specification. The naming of the bismuth-boron-selenium glass frit is similar.

[0070] In some embodiments, the additive is also called a glass modifier because it is used to modify the glass system. In the process of manufacturing glass frit, a glass former is used to form the initial network structure of the glass. When the additive is incorporated into the glass network structure, the initial network structure formed by the glass former is changed, thereby changing the original properties such as thermal performance of the glass. The additive may be an oxide of any one element selected from an alkali metal element, an alkaline earth metal element, and a transition metal element, or a mixture of oxides of multiple elements. Exemplarily, the additive is any one or more selected from the group consisting of PbF2, BiF3, SiO2, Bi2O3, AgO2, Ag2O, AgO, ZnO, MgO, CaO, Al2O3, Li2O, Na2O, K2O, Rb2O, Ce2O, and Fe2O3. In some embodiments, the additive may be a combination of SiO2, Bi2O3, Li2O, Na2O, Al2O3, ZnO, etc. The content of each component in the additive can be adjusted according to the desired glass performance. The fluorine ions and oxygen ions in the additive are both anions and can be used in combination with the above metal cations.

[0071] In some embodiments, the content of the additive in the lead-boron-selenium glass frit may be 0.5%-20%, 5%-19%, 8%-17%, 10%-16%, 14.2%-15.7%, or 14.7%-15.3%, calculated based on the dry weight of the lead-boron-selenium glass frit. The percentage is by weight. The content adjustment is required to ensure that the sum of the contents of each component in the lead-boron-selenium glass frit is 100 wt%.

[0072] It should be ensured that the various components of the glass frit (including the base components and additives) are inert to the aluminum powder in the conductive paste composition. More specifically, it should be ensured that each component in the glass frit does not prematurely react with the aluminum powder in the conductive paste so as not to affect the conductive performance and efficiency of the fabricated photovoltaic device. In the research, the inventors surprisingly found that SeO2 added to the lead-boron-selenium glass frit can lower the Tg point of the glass frit and not excessively oxidize the aluminum powder in the silver-aluminum paste, allowing a low resistance electrical contact to be formed in a photovoltaic device such as a solar cell. Therefore, the embodiment of the present application creatively provides a lead-boron-selenium glass frit instead of the conventional lead-silicon-boron glass frit.

[0073] In some embodiments, the conductive paste composition and lead-boron-selenium glass frit of the present application contain 1.2 wt% or less TeO2, or 1.0 wt% or less TeO2, or 0.5 wt% or less TeO2. The weight percentages are the wt% of TeO2 as a percentage of the total dry weight of the lead-boron-selenium glass frit. The content adjustment is necessary to ensure that the sum of the contents of each component of the lead-boron-selenium glass frit is 100 wt%.

[0074] In some other embodiments, the conductive paste compositions and lead-boron-selenium glass frits of the present application do not contain any form of elemental tellurium (Te), such as TeO2.

[0075] In some embodiments, the lead-boron-selenium oxide in the lead-boron-selenium glass frit may be in a completely amorphous state or may be partially amorphous and partially crystalline during sintering, and the content of the crystalline portion of the lead-boron-selenium oxide in the lead-boron-selenium glass frit may be 1.5% or less, and may be 1% or less, of the total weight of the lead-boron-selenium oxide, which is useful for the subsequent metallization process of the battery cell.

[0076] In some other embodiments, the lead-boron-selenium glass frit of the present application may further contain Cd and / or Tl elements. Although Cd and / or Tl elements can also lower the Tg point of the glass frit, it is preferable not to add too much of them because of their high toxicity. Therefore, the lead-boron-selenium glass frit may contain less than 100 ppm of CdO or Tl2O3, less than 50 ppm of CdO or Tl2O3, less than 20 ppm of CdO or Tl2O3, or no CdO or Tl2O3.

[0077] In some embodiments, the method for producing the lead-boron-selenium glass frit is to mix the above oxides according to the required weight ratio, then sinter them at high temperature to make them in a molten state, mix the melt uniformly, then anneal quickly, and grind to form the lead-boron-selenium glass frit in powder form. In order to facilitate uniform mixing in the process of producing the conductive paste, the particle size of the lead-boron-selenium glass frit powder is preferably not too large, and the D of the lead-boron-selenium glass frit powder is preferably 0.01 to 0.01 mm. 50 may be 0.5 to 3.0 micrometers.

[0078] Conductive Components In some embodiments, the conductive component is used to perform a conductive function after forming the photovoltaic device. The conductive component may be one or more mixtures selected from elemental silver, elemental copper, silver alloys, copper alloys, and silver salts. If the conductive component is a silver salt, the silver salt may be selected from AgCl, AgNO3, AgOOCH3 (silver acetate), silver trifluoroacetate, or silver orthophosphate (Ag3PO4).

[0079] In some embodiments, the conductive component may be present in the form of a sheet, a particle, a colloid, etc. When present in the form of a particle, it is preferable that the particle size of the conductive component is not too large so as not to affect dispersibility. In some embodiments, the average particle size of the conductive component may be in the micrometer scale range, exemplarily 15 micrometers or less, 10 micrometers or less, 5 micrometers or less, 2 micrometers or less, or in the range of 0.1 micrometers to 1 micrometer. In other embodiments, the average particle size of the conductive component may be in the nanoscale range, exemplarily 800 nanometers or less, 700 nanometers or less, 500 nanometers or less, 300 nanometers or less, 200 nanometers or less, 50 nanometers or less, or in the range of 10 nanometers to 20 nanometers.

[0080] In some other embodiments, the weight percentage of the conductive component in the total solid matter of the conductive paste composition may be 87% to 99%, 88% to 98%, 90% to 97%, 91% to 96%, 92% to 95%, or even 93% to 94%. The proportion of the conductive component in the total solid matter of the conductive paste composition is adjusted to ensure that the sum of the weight percentages of each component in the conductive paste composition is 100%.

[0081] Aluminum single component In some embodiments, aluminum element is a necessary component in the conductive paste composition. The aluminum element component may be aluminum powder. The aluminum element component and the conductive component are dispersed in an organic medium, and the aluminum powder helps to form an ohmic contact with low resistivity during high-temperature sintering. Exemplarily, if the conductive component is silver element, the n-type conductive paste composition contains silver aluminum paste (Ag / Al paste), and the p-type conductive paste does not contain metallic aluminum element and therefore contains only silver paste (Ag paste).

[0082] During the sintering process in the manufacture of n-type photovoltaic devices, one of the roles of aluminum in the conductive paste composition is to promote electrical contact with the p-type semiconductor (e.g., p-type emitter) of the photovoltaic device, so it is very important to maintain the metallic aluminum element during the sintering process. In order to improve the efficiency of the photovoltaic device, the electrical contact should have a low resistivity (e.g., 0.5-5 mohm / cm 2 ) is required. The conductive paste composition contains an oxidizing component (e.g., glass frit) for etching the passivation film. If the oxidizing component reacts excessively with the aluminum element during the sintering process, the resistance value of the conductive paste composition and the P-type emitter increases, thereby reducing the efficiency of the photovoltaic device, so the oxidizing component in the conductive paste composition must not excessively oxidize the aluminum element during the sintering process. The lead-boron-selenium glass frit of the present application contains selenium element (Se), which has a lower melting point than its homologous tellurium element (Te), and therefore helps to lower the melting point of the lead-boron-selenium glass frit and improve its fluidity, making it easier to perform screen printing and etching the passivation film. In addition, SeO2 contained in the lead-boron-selenium glass frit does not excessively oxidize the aluminum element like TeO2, so that the aluminum element and the p-type emitter make low-resistance electrical contact, which helps to improve the efficiency of the photovoltaic device.

[0083] In some embodiments, in the first conductive paste composition, the aluminum simplex component may account for 0.5% to 3%, 0.8% to 2.9%, 0.9% to 2.8%, 1.0% to 2.5%, 1.2% to 2.4%, 1.5% to 2.1%, or 1.6% to 2.0% of the total solid matter of the first conductive paste composition. The proportion of the aluminum simplex component in the total solid matter of the conductive paste composition must be adjusted to ensure that the sum of the weight percentages of each component in the conductive paste composition is 100%.

[0084] In some embodiments, the aluminum component may be mixed with other components of the conductive paste composition in powder form. The average particle size of the aluminum component may be on the micrometer scale. As the aluminum component on the micrometer scale, the particle size range may be 5 micrometers or less, 4 micrometers or less, 3 micrometers or less, 2 micrometers or less, or may be within the range of 1 micrometer to 5 micrometers.

[0085] organic medium In some embodiments, for a solid material composed of a conductive component, a lead-boron-selenium glass frit, and an aluminum simple component, an organic medium is used as a liquid phase in the conductive paste composition to disperse the conductive component, the lead-boron-selenium glass frit, and the aluminum simple component to form a paste having a certain viscosity. Depending on the viscosity and rheology of the paste, the conductive component, the lead-boron-selenium glass frit, and the aluminum simple component can be dispersed in the paste for a long period of time and stably, and the conductive paste composition can be dispersed in a printing screen and applied in a desired pattern on the surface of a passivation film of a photovoltaic device by a screen printing method.

[0086] In some embodiments, the organic medium is pyrolyzed during high temperature sintering after screen printing. The organic medium may include a polymer and an organic solvent. The polymer may include cellulose, resin, esters, etc. The organic solvent may include α-terpene, β-terpene, dibutyl phthalate, butyl carbitol, butyl carbitol acetate, hexylene glycol, etc. The cellulose may include ethyl cellulose, ethyl hydroxyethyl cellulose, or mixtures thereof. The resin may include wood rosin or phenolic resin, or mixtures thereof. The esters may include polymethacrylates of lower alcohols, etc.

[0087] In some embodiments, the content of the organic medium in the conductive paste composition depends on the viscosity, rheology, and physical properties required for the entire conductive paste composition. The content of the organic medium may be 6% to 12%, 7% to 11%, or 8% to 10% of the total weight of the conductive paste composition. The percentages are weight percentages.

[0088] In some embodiments, the n-Type conductive paste composition of the present application includes lead-boron-selenium glass frit (also called Pb-B-Se oxide), silver powder, aluminum powder, and an organic medium. The lead-boron-selenium glass frit contains at least lead, boron, and selenium elements, and is used to etch or corrode the passivation film during high-temperature sintering. The organic medium belongs to the dispersing phase and is used to disperse the lead-boron-selenium glass frit, silver powder, and aluminum powder. The conductive paste composition in the embodiments of the present application can etch and penetrate the passivation film of the photovoltaic device after sintering, and make a low-resistance contact with the p-type semiconductor. This is an effect that is difficult to achieve with conventional conductive pastes that do not contain aluminum. One of the reasons is that the conductive paste that does not contain aluminum powder is difficult to make a low-resistance electrical contact with the p-type semiconductor after penetrating the passivation film of the photovoltaic device, which may ultimately affect the efficiency of the photovoltaic device.

[0089] Tellurium oxide can lower the softening point of the glass system in the lead tellurium glass paste and improve the fluidity of the glass system, but tellurium oxide can oxidize the aluminum element in the silver aluminum paste to aluminum oxide (Al2O3), which may not be able to make good electrical contact in the photovoltaic device, which affects the efficiency of the photovoltaic device, so tellurium oxide cannot be used in the n-type conductive paste containing the silver aluminum paste. Although selenium and tellurium are homologous elements, the inventors have surprisingly found in their research that selenium oxide does not oxidize the aluminum metal element in the silver aluminum paste in the subsequent sintering process, unlike tellurium oxide, and this can meet the requirement that the n-type conductive paste composition and the p-type semiconductor make a low-resistance contact.

[0090] The inventors further found that selenium oxide, which is one of glass formers and has a low melting temperature, can be added to change the thermal performance of the conductive paste glass frit. Compared with an n-type conductive paste composition without selenium oxide, adding selenium oxide can lower the Tg point and melting temperature and improve the fluidity, thereby meeting the requirements for etching the passivation film. This is because the glass paste needs to soften and flow at a high speed during the sintering process, which helps to achieve controllable etching of the passivation film. Tellurium (Te) added to lead tellurium glass (Pb-Te) can also improve the fluidity and lower the softening point, but as mentioned above, tellurium oxide oxidizes aluminum metal element and reduces the conductive contact performance of aluminum, so tellurium oxide is not suitable as an additive to be added to the lead-boron-selenium glass frit in the examples of the present application.

[0091] Also, currently, thallium element (Tl) can be used to lower the melting temperature of the conductive paste composition and improve its fluidity, but thallium element cannot be added in large quantities because it is highly toxic, harmful to the human body and the environment, and has high recovery costs. Selenium oxide used in some embodiments of the present application is less toxic and can lower the melting temperature and improve the fluidity instead of thallium oxide. However, this does not mean that Se element cannot be used in combination with Cd element and / or Tl element. In some embodiments of the present application, Cd element and / or Tl element (e.g., CdO or Tl2O3) can be added to lead-boron-selenium glass frit (containing Se element), but it is necessary to ensure that the content of Cd element and / or Tl element is less than 100 ppm or less, for example, less than 10 ppm. In some embodiments of the present application, Cd and / or Tl elements in any form, including but not limited to CdO or Tl2O3, may be directly added to the conductive paste composition (containing Se element), but it is necessary to ensure that the conductive paste composition contains 100 ppm or less of Cd and / or Tl element to avoid excessive toxicity. By the above method, the conductive paste composition can be controlled within a low toxicity range.

[0092] Therefore, the lead-boron-selenium glass frit (containing Pb-B-Se oxide) in each example of the present application can be used in place of the known lead-boron-selenium glass frit (containing Pb-Si-B oxide) in combination with a silver-aluminum paste to produce an n-type conductive paste composition that can penetrate the passivation film and make good electrical contact with the p-type semiconductor below the passivation film when manufacturing a photovoltaic device.

[0093] Method for producing first conductive paste composition Some embodiments of the present application further provide a method for preparing the first conductive paste composition, comprising: mixing the conductive component, the lead-boron-selenium glass frit and the aluminum simplex component according to the above blending ratio, dispersing in a certain amount of organic medium, and forming the first conductive paste composition after uniform dispersion. The blending ratio of the lead-boron-selenium glass frit, the conductive component and the aluminum simplex component needs to be adjusted to ensure that the sum of the weight percentages of the three components in the total solid matter of the conductive paste composition is 100%.

[0094] Application of the first type of conductive paste composition The conductive paste composition in some embodiments of the present application can be used in the manufacture of photovoltaic devices, such as solar cells. Illustratively, the conductive paste composition quickly etches the passivation film of the photovoltaic device during the sintering process, and finally penetrates the passivation film to make electrical contact with the p-type semiconductor of the photovoltaic device with low resistivity. The p-type semiconductor may be a p-type emitter that is preferably manufactured from a silicon substrate by a diffusion method.

[0095] Photovoltaic devices of the first kind As shown in FIG. 1, some embodiments of the present application provide a first type of photovoltaic device, which is an n-PERT solar cell (Passivated Emitter, Rear Totally Diffused), and uses the first type of conductive paste composition in the above embodiments during manufacture.

[0096] As shown in Figure 1c, the n-PERT solar cell has (1) an n-type crystalline silicon substrate 100 located in the middle of an n-PERT solar cell; (2) a front p-type emitter 101 located on the front side of the n-type crystalline silicon substrate 100; (3) a front passivation film 103 deposited on the surface of the front p-type emitter 101; (4) a back surface field 102 located on the back surface of the n-type crystalline silicon substrate 100; (5) a back surface passivation film 104 deposited on the surface of the back surface field 102; (6) a front conductive structure 107 penetrating at least a portion of the front passivation film 103 on the surface of the front p-type emitter 101 and electrically connecting to the front p-type emitter 101; (7) A back surface conductive structure 108 that penetrates at least a portion of the back surface passivation film 104 on the surface of the back surface field 102 and makes an electrical connection with the back surface field 102 .

[0097] The above numbers do not indicate the relative positions of the structures.

[0098] The n-type crystalline silicon substrate 100, the front side p-type emitter 101, the back surface field 102, the front side passivation film 103 and the back side passivation film 104 are collectively referred to as a semiconductor workpiece 110 (also referred to as an n-type semiconductor substrate).

[0099] The n-type crystalline silicon substrate 100 is also called an n-type lightly doped substrate, and is an n-type solar cell blue film formed by lightly doping and diffusing a silicon wafer using a phosphorus source.

[0100] The front p-type emitter 101, also called p-type semiconductor, is formed by doping a trivalent element into an n-type crystalline silicon substrate 100 by a diffusion method. The trivalent element may be boron or gallium. Acceptor impurity sources for providing elemental boron include diboron trioxide, boron nitride, trimethyl borate, tripropyl borate, boron tribromide, or diborane. The same is true for elemental gallium.

[0101] The back surface field 102 is formed by doping a pentavalent element (e.g., phosphorus) into the n-type crystalline silicon substrate 100 by a diffusion method. The donor impurity source for providing the phosphorus element may be diphosphorus pentoxide, phosphorus oxychloride, phosphorus trichloride, or phosphine.

[0102] The front passivation film 103 and the back passivation film 104 may also be called insulating layers or anti-reflective layers, and may be made of silicon nitride, aluminum oxide, titanium oxide, or silicon oxide, or any combination thereof. The passivation films may be deposited on one or two surfaces of the n-type crystalline silicon substrate 100 by vapor deposition, sputtering, or other methods.

[0103] The front conductive structure 107 is formed by using a first conductive paste composition. The first conductive paste composition (for example, the front silver-aluminum paste 105 shown in FIG. 1) is applied to at least a part of the surface of the front passivation film 103 in the form of a desired pattern, and during subsequent sintering, the first conductive paste composition etches through the surface of the front passivation film 103 that contacts the first conductive paste composition, and makes electrical contact with the front p-type emitter 101 to form a front conductive structure 107 (also called a front silver-aluminum electrode) in the form of a conductive metal contact.

[0104] Metallized silver paste, such as silver paste containing Pb-Te-O glass powder, which is commercially applied to p-type crystalline silicon batteries, may be used as the backside conductive structure 108. A conductive paste composition (e.g., backside conductive structure 108) is applied to at least a part of the surface of the backside passivation film 104 in the form of a desired pattern, and in the subsequent sintering process, the conductive paste composition etches through the surface of the backside passivation film 104 that contacts the first conductive paste composition, and makes electrical contact with the backside electric field 102, thereby forming the backside conductive structure 108 (also called backside silver electrode) in the form of a conductive metal contact.

[0105] One of the purposes of the sintering is to pyrolyze the organic medium in the first conductive paste composition and sinter the metal powder. The sintering can be carried out in air or an oxygen-containing atmosphere. During sintering, the organic medium in the first conductive paste composition is pyrolyzed, and the glass frit therein gradually etches the portion of the passivation film that contacts the first conductive paste composition, and after the etching is completed, the first conductive paste composition penetrates the passivation film and forms a conductive structure after cooling. The conductive paste composition contains a silver-aluminum paste, and the silver component therein has high conductivity. One of the roles of the aluminum powder is to facilitate the front p-type emitter 101 and the front conductive structure 107 to make a low-resistance electrical connection, thereby providing the photovoltaic device with the desired efficiency.

[0106] As shown in FIG. 1a to FIG. 1c, the method for manufacturing the n-PERT solar cell includes: Step (1) of providing an n-type crystalline silicon substrate 100 formed by lightly doping a crystalline silicon wafer (e.g., a polycrystalline silicon wafer or a single crystal silicon wafer) using a phosphorus source; (2) doping a front surface of the n-type crystalline silicon substrate 100 with a trivalent element (e.g., boron or gallium) by diffusion to form a front p-type emitter 101 on the front surface of the n-type crystalline silicon substrate 100, and doping a back surface of the n-type crystalline silicon substrate 100 with a pentavalent element (e.g., phosphorus) by diffusion to form a back surface field 102; (3) depositing a front passivation film 103 on the surface of the front p-type emitter 101 and a back surface passivation film 104 on the surface of the back surface field 102; Step (4) of applying a first conductive paste composition as a front silver-aluminum paste 105 in the form of a pattern on at least a part of the surface of the front passivation film 103, and applying a metallized silver paste, such as a silver paste containing Pb-Te-O glass powder, which is commercially applied to p-type crystalline silicon batteries, as a back metallized paste 106 in the form of a pattern on at least a part of the surface of the back passivation film 104; and (5) sintering, etching through the front silver-aluminum paste 105 at the surface of the front passivation film 103 in contact with the front silver-aluminum paste 105 to form a front conductive structure 107 (also called front silver-aluminum electrode) in electrical contact with the front p-emitter 101 and in the form of a conductive metal contact, and etching through the back metallization paste 106 at the surface of the back passivation film 104 in contact with the back metallization paste 106 to form a back conductive structure 108 (also called back silver electrode) in the form of a conductive metal contact, thereby obtaining an n-PERT solar cell.

[0107] The numbers of the above steps do not limit the order of the steps.

[0108] In the sintering process of step (5), the degree to which the silver-aluminum paste is converted into a molten state and penetrates the passivation film depends on the composition and thickness of the passivation film, the composition of the silver-aluminum paste itself, and the sintering conditions. The sintering temperature may be in the range of 700 to 850°C, for example, 710°C, 720°C, 750°C, 780°C, 800°C, 815°C, 820°C, 835°C, etc. The individual sintering times may be in the range of 1 second to 5 minutes, for example, in the range of 1 second to 5 seconds, or in the range of 1 minute to 2 minutes. If the sintering time is too short, the silver-aluminum paste is difficult to penetrate the passivation film. If the sintering time is too long, the silver-aluminum paste will corrode other structures after penetrating the passivation film, thereby damaging the photovoltaic device. Therefore, during sintering, the silver-aluminum paste needs to corrode or etch the passivation film at a controllable rate. By sintering, the organic medium of the silver-aluminum paste is thermally decomposed, and the aluminum powder in the silver-aluminum paste melts and flows to the p-type semiconductor interface, reacts with the p-type semiconductor, and promotes the formation of low-resistivity electrical contact. In order not to corrode the p-type semiconductor and damage the internal structure of the photovoltaic device, the etching process cannot last for a long time. The entire sintering process includes individual sintering processes, but also includes the processes of sintering from low temperature to high temperature and cooling, so it takes more than 10 seconds.

[0109] Photovoltaic devices of the second kind As shown in FIG. 2, some embodiments of the present application provide a second type of photovoltaic device, which is a tunnel oxide passivated contact solar cell (n-TOPCon), and utilizes the first type of conductive paste composition during manufacture.

[0110] As shown in Figure 2c, the n-TOPCon solar cell has (1) an n-type crystalline silicon substrate 200 located in the middle of the n-TOPCon solar cell; (2) a front p-type emitter 201 located on the front side of an n-type crystalline silicon substrate 200; (3) a front passivation film 203 deposited on the front surface of the front p-type emitter 201; (4) a tunnel passivation film 202a located on the back surface of the n-type crystalline silicon substrate 200; (5) The n-type semiconductor layer 202a is located on the surface of the tunnel passivation film 202a. + A polycrystalline silicon layer 202b; (6)n + a back surface passivation film 204 deposited on the surface of the polycrystalline silicon layer 202b; (7) a front conductive structure 207 penetrating at least a portion of the front passivation film 203 on the surface of the front p-type emitter 201 and electrically connecting with the front p-type emitter 201; (8)n + At least a part of the back surface passivation film 204 on the front surface of the polycrystalline silicon layer 202b is penetrated, and the n + and a backside conductive structure 208 that makes electrical connection with polysilicon layer 202b.

[0111] The above numbers do not indicate the relative positional relationship between each structure. For the parts of the n-TOPCon solar cell that are similar to those of the n-PERT solar cell, please refer to the explanation for the n-TOPCon solar cell, and the explanation will be omitted here.

[0112] An n-type crystalline silicon substrate 200 (also called an n-type lightly doped substrate), a front p-type emitter 201 (also called a p-type semiconductor), a tunnel passivation film 202a, + The polysilicon layer 202b, the front side passivation film 203 and the back side passivation film 204 are collectively referred to as a semiconductor workpiece 210 (also referred to as an n-type semiconductor substrate).

[0113] In the n-TOPCon solar cell, the tunnel passivation film 202a and the n + A polycrystalline silicon layer 202b is formed.

[0114] The front conductive structure 207 is formed by using a first conductive paste composition. The first conductive paste composition (e.g., front silver-aluminum paste 205) is applied to at least a part of the surface of the front passivation film 203 in the form of a desired pattern, and in the subsequent sintering process, the first conductive paste composition etches through the surface of the front passivation film 203 that contacts the first conductive paste composition, and makes electrical contact with the front p-type emitter 201 to form a front conductive structure 207 (also called a front silver-aluminum electrode) in the form of a conductive metal contact.

[0115] The back conductive structure 208 may be a metallized silver paste, such as a silver paste containing Pb-Te-O glass powder, which is commercially applied to p-type crystalline silicon cells. A conductive paste composition (e.g., back metallization paste 206) is applied to at least a part of the surface of the back passivation film 204 in the form of a desired pattern, and in the subsequent sintering process, the first conductive paste composition etches through the surface of the back passivation film 204 that contacts the first conductive paste composition, forming n + Electrical contact is made with the polysilicon layer 202b to form a backside conductive structure 208 (also called a backside silver electrode) in the form of a conductive metal contact.

[0116] As shown in FIG. 2a to FIG. 2c, the method for manufacturing the n-TOPCon solar cell includes: Step (1) of providing an n-type crystalline silicon substrate 200 formed by lightly doping a crystalline silicon wafer using a phosphorus source; A front p-type emitter 201 is formed on the front surface of the n-type crystalline silicon substrate 200 by doping the front surface of the n-type crystalline silicon substrate 200 with a trivalent element (e.g., boron or gallium) by a diffusion method, and a tunnel passivation film 202a and a n-type p-type emitter 202b are formed on the front surface of the n-type crystalline silicon substrate 200 by using a tunnel oxide (e.g., SiO2) by a tunnel passivation contact method. + Polycrystalline silicon layer 202b(n +(2) forming a poly-Si (poly-Si); A front passivation film 203 is deposited on the surface of the front p-type emitter 201, and + (3) depositing a back surface passivation film 204 on the surface of the polycrystalline silicon layer 202b; Step (4) of applying a first conductive paste composition as a front silver-aluminum paste 205 in the form of a pattern on at least a part of the surface of the front passivation film 203, and applying a metallized silver paste, such as a silver paste containing Pb-Te-O glass powder, which is commercially applied to p-type crystalline silicon batteries, as a back metallized paste 206 in the form of a pattern on at least a part of the surface of the back passivation film 204; Sintering is performed, the front silver-aluminum paste 205 is etched through the surface of the front passivation film 203 that contacts the front silver-aluminum paste 205, making electrical contact with the front p-type emitter 201 and forming a front silver-aluminum electrode in the form of a conductive metal contact, the back metallization paste 206 is etched through the surface of the back passivation film 204 that contacts the back metallization paste 206, and forming an n + and (5) forming a back electrode in the form of a conductive metal contact, making electrical contact with the polycrystalline silicon layer 202b, thereby obtaining an n-TOPCon solar cell.

[0117] The above step numbers do not limit the order of the steps.

[0118] [Second type conductive paste composition] The present application further provides a second conductive paste composition capable of forming a low-resistance electrical connection with a P-type semiconductor of a photovoltaic device. The second conductive paste composition uses bismuth oxide instead of lead oxide, and therefore its toxicity is further reduced compared to the first conductive paste composition. In the above description of the second conductive paste composition, the same parts as those of the first conductive paste composition are incorporated herein by reference. Preferably, the second conductive paste composition of the present application and the bismuth-boron-selenium glass frit contained therein do not contain any form of elemental tellurium (Te), such as tellurium oxide (TeO2). The second conductive paste composition will be specifically described below.

[0119] A second type of conductive paste composition according to some embodiments of the present application includes: (1) a bismuth-boron-selenium glass frit; (2) a conductive component; (3) an aluminum component; (4) An organic medium.

[0120] The bismuth-boron-selenium glass frit, the conductive component, and the aluminum component are the solid components of the conductive paste composition, and the sum of the weight percentages of the three is 100%. The organic medium is a dispersed phase in the conductive paste composition and provides printing performance.

[0121] Bismuth-boron-selenium glass frit In some embodiments, the bismuth-boron-selenium glass frit is a composition having a glass component, and may account for 0.5% to 10% of the total solid matter of the conductive paste composition. In other embodiments, the proportion of the bismuth-boron-selenium glass frit may be 0.8% to 9.8%, 1% to 9.5%, 1.5% to 9%, 2% to 8%, 3% to 7%, 4% to 6%, or 5% to 5.5%. The percentage of each component in the conductive paste composition is expressed as a weight percentage (wt%). The proportion of the bismuth-boron-selenium glass frit in the total solid matter of the conductive paste composition needs to be adjusted to ensure that the sum of the weight percentages of each component in the conductive paste composition is 100%.

[0122] In some embodiments, the bismuth-boron-selenium glass frit contains at least 50%-90% Bi2O3, 2%-35% B2O3, and 0.1%-15% SeO2. The percentage of each component in the glass frit is expressed by weight (wt%), and all are calculated based on the dry weight of the bismuth-boron-selenium glass frit. Adjustment of the proportion of each component in the bismuth-boron-selenium glass frit is necessary to ensure that the sum of each component is 100%.

[0123] In some embodiments, calculated based on the dry weight of the bismuth-boron-selenium glass frit, the content (wt%) of Bi2O3 in the bismuth-boron-selenium glass frit may be 52% to 90%, 55% to 88%, 58% to 85%, 60% to 80%, 66.6% to 75%, 68.9% to 71.3%, or even 70% to 71%. Bi2O3 plays the role of PbO in the glass frit, and can change its thermal performance, reduce its melting temperature, and improve its fluidity, etc., and has low toxicity, so it can be used instead of PbO to further reduce the toxicity of the glass frit, but Bi2O3 does not replace PbO in a 1:1 ratio and needs to be selected according to specific circumstances.

[0124] In some embodiments, the content (wt%) of B2O3 in the bismuth-boron-selenium glass frit may be 2%-20%, 3%-18%, 5%-16%, 7%-15%, 10.5%-12%, 10.9%-11.6%, or 11.1%-11.3%, calculated based on the dry weight of the bismuth-boron-selenium glass frit. The adjustment of the content is required to ensure that the sum of the contents of each component in the bismuth-boron-selenium glass frit is 100%.

[0125] In some embodiments, the content (wt%) of SeO2 in the bismuth-boron-selenium glass frit may be 0.1% to 15%, 0.2% to 14%, 1% to 13%, 2% to 12.4%, 3.1% to 9.3%, or even 3.5% to 6.2%, calculated based on the dry weight of the bismuth-boron-selenium glass frit.

[0126] In some embodiments, in addition to the three basic components, the bismuth-boron-selenium glass frit may further contain an additive. The additive may be an oxide of any one element selected from an alkali metal element, an alkaline earth metal element, and a transition metal element, or a mixture of oxides of multiple elements. Exemplarily, the additive is any one or multiple elements selected from the group consisting of SiO2, BiF3, AgO2, Ag2O, AgO, ZnO, MgO, CaO, Al2O3, Li2O, Na2O, KO, Rb2O, Ce2O, and Fe2O3. "Multiple types" includes any two types of components, any three types of components, any four types of components, etc., or all of the components. The content of each component in the additive can be adjusted according to the desired glass performance.

[0127] In some embodiments, the total content of the additives may be 0.1% to 25%, 2% to 20%, 5% to 15%, 8% to 12%, 10.5% to 11.7%, or even 10.9% to 11.2%, calculated based on the dry weight of the bismuth-boron-selenium glass frit.

[0128] In some embodiments, when the additive contains Li2O, the content of Li2O may be 0.1%-5%, 0.2%-4.5%, 0.5%-4%, 0.7%-3.5%, 1%-3%, 1.5%-2.5%, or 2%-2.2%, calculated based on the dry weight of the bismuth-boron-selenium glass frit. The percentage of each component in the glass frit is weight percentage (wt%).

[0129] In some other embodiments, if the additive contains Na2O, the content of Na2O may be 0.1% to 5%, 0.2% to 4.7%, 0.3% to 4.5%, or even 0.5% to 4%, or 0.7% to 3.5%, 1% to 3%, 1.5% to 2.5%, or 2% to 2.2% when calculated based on the dry weight of the bismuth-boron-selenium glass frit. Li2O and Na2O are oxides of alkali metals, have low melting points, and can lower the melting temperature of the glass frit and improve its fluidity, so they can be used as components of the additive. The adjustment of the content needs to ensure that the sum of the contents of each component of the bismuth-boron-selenium glass frit is 100 wt%.

[0130] In some other embodiments, if the additive contains ZnO, the content of ZnO may be 0.1% to 20%, 0.5% to 19%, 0.8% to 15%, or even 1% to 12%, or 2% to 10%, 3% to 8%, 5% to 9%, or 6% to 8%, calculated based on the dry weight of the bismuth-boron-selenium glass frit. ZnO belongs to the oxides of transition metals and can be used as a glass modifier to modify the original thermal performance of glass, so it can also be a component of the additive. The remaining components of the additive are similar.

[0131] It should be ensured that the various components of the glass frit (including the basic components and additives, etc.) are inert to the silver-aluminum paste in the conductive paste composition. More specifically, it should be ensured that each component in the glass frit does not prematurely react with the aluminum powder in the silver-aluminum paste so as not to affect the conductive performance and efficiency of the fabricated photovoltaic device. In the research, the inventors surprisingly found that SeO2 added to the bismuth-boron-selenium glass frit can lower the Tg point of the glass frit and not over-oxidize the aluminum powder in the silver-aluminum paste, allowing a low-resistance electrical contact to be formed in a photovoltaic device such as a solar cell. Therefore, some embodiments of the present application creatively provide a bismuth-boron-selenium glass frit which replaces the conventional lead-silicon-boron glass frit and is less toxic than the aforementioned lead-boron-selenium glass frit, and can meet the requirements of a photovoltaic device with low toxicity.

[0132] In some embodiments, the bismuth-boron-selenium oxide in the bismuth-boron-selenium glass frit may be in a completely amorphous state or may be partially amorphous and partially crystalline during sintering. The content of the crystalline portion of the bismuth-boron-selenium oxide in the bismuth-boron-selenium glass frit accounts for 1.5% or less of the total weight of the bismuth-boron-selenium oxide, and may account for 1% or less, which is useful for subsequent screen printing and etching processes.

[0133] In some embodiments, the method for preparing the bismuth-boron-selenium glass frit is to mix the above oxides according to the required weight ratio, then sinter them at high temperature to make them in a molten state, mix the melt uniformly, and then anneal them quickly and grind them to form the bismuth-boron-selenium glass frit in powder form. In order to facilitate uniform mixing in the process of preparing the conductive paste, the grain size of the bismuth-boron-selenium glass frit powder is preferably not too large, and the D of the bismuth-boron-selenium glass frit powder is preferably 0.1 to 0.5 μm. 50may be 0.5 to 3.0 micrometers.

[0134] Conductive Components In some embodiments, the conductive component is used to perform the role of electrical conductivity after forming the photovoltaic device. The conductive component may be one or more mixtures selected from elemental silver, silver alloys, and silver salts. The silver salts may be selected from AgCl, AgNO3, AgOOCH3 (silver acetate), silver trifluoroacetate, or silver orthophosphate (Ag3PO4).

[0135] In some embodiments, the conductive component may be present in the form of a sheet, a particle, a colloid, or the like. If present in the form of a particle, it is preferable that the particle size of the conductive component is not too large so as not to affect dispersibility. In some embodiments, the average particle size of the conductive component may be in the micrometer scale range, exemplarily 15 micrometers or less, 10 micrometers or less, 5 micrometers or less, 2 micrometers or less, or in the range of 0.1 micrometers to 1 micrometer. In other embodiments, the average particle size of the conductive component may be in the nanoscale range, exemplarily 800 nanometers or less, 700 nanometers or less, 500 nanometers or less, 300 nanometers or less, 200 nanometers or less, 50 nanometers or less, or in the range of 10 nanometers to 20 nanometers.

[0136] In some other embodiments, the weight percentage of the conductive component in the total solid matter of the conductive paste composition may be 87% to 99%, 88% to 98%, 90% to 97%, 91% to 96%, 92% to 95%, or even 93% to 94%. The proportion of the conductive component in the total solid matter of the conductive paste composition is adjusted to ensure that the sum of the weight percentages of each component in the conductive paste composition is 100%.

[0137] Aluminum single component In some embodiments, the conductive paste composition includes an aluminum element as a necessary component. The aluminum element component may be aluminum powder. The aluminum element component and the conductive component are dispersed in an organic medium, and the aluminum powder helps to form an ohmic contact with low resistivity during a high-temperature sintering process. Exemplarily, if the conductive component is silver element, the conductive paste composition includes a silver-aluminum paste (Ag / Al paste).

[0138] In their research, the inventors have found that the oxidizable components in the first conductive paste composition and the second conductive paste composition in each embodiment of the present application do not excessively oxidize the aluminum powder, and have low melting temperatures and high fluidity, and can meet the requirements of screen printing and etching of passivation films, and aluminum alone can also make low-resistance electrical contact with the p-type emitter, thereby providing the photovoltaic device with excellent efficiency.

[0139] In the second type of conductive paste composition, the aluminum simple component may account for 0.5% to 3%, 0.8% to 2.9%, 0.9% to 2.8%, 1.0% to 2.5%, 1.2% to 2.4%, 1.5% to 2.1%, or 1.6% to 2.0% of the total solid matter of the second type of conductive paste composition. The proportion of the aluminum simple component in the total solid matter of the conductive paste composition must be adjusted to ensure that the sum of the weight percentages of each component in the conductive paste composition is 100%.

[0140] In some embodiments, the aluminum component may be mixed with other components of the conductive paste composition in powder form. The average particle size of the aluminum component may be on the micrometer scale. As the aluminum component on the micrometer scale, the particle size range may be 5 micrometers or less, 4 micrometers or less, 3 micrometers or less, 2 micrometers or less, or may be within the range of 1 micrometer to 5 micrometers.

[0141] organic medium In some embodiments, for a solid material composed of a conductive component, a bismuth-boron-selenium glass frit, and an aluminum simple component, an organic medium is used as a liquid phase in the conductive paste composition to disperse the conductive component, the bismuth-boron-selenium glass frit, and the aluminum simple component to form a paste having a certain viscosity. During the high-temperature sintering process after screen printing, the organic medium is thermally decomposed.

[0142] In some embodiments, the organic medium may include a polymer and an organic solvent. The polymer may include cellulose, resins, esters, and the like. The organic solvent may include alpha-terpene, beta-terpene, dibutyl phthalate, butyl carbitol, butyl carbitol acetate, hexylene glycol, and the like. The cellulose may include ethyl cellulose, ethyl hydroxyethyl cellulose, or mixtures thereof. The resin may include wood rosin or phenolic resin, or mixtures thereof. The esters may include polymethacrylates of lower alcohols, and the like.

[0143] In some embodiments, the content of the organic medium in the n-type conductive paste composition depends on the viscosity, rheology, and physical properties required for the entire n-type conductive paste composition. The content of the organic medium may be 10% to 40%, 12% to 38%, 15% to 35%, or even 20% to 30% of the total weight of the conductive paste composition. The percentages are weight percentages.

[0144] The conductive paste composition in some embodiments of the present application includes bismuth-boron-selenium glass frit (Bi-B-Se oxide), silver powder, aluminum powder, and an organic medium. The bismuth-boron-selenium glass frit contains bismuth, boron, and selenium elements, and is used to etch or corrode the passivation film during high-temperature sintering. The organic medium belongs to the dispersing phase and is used to disperse the bismuth-boron-selenium glass frit, silver powder, and aluminum powder. The conductive paste composition in some embodiments of the present application can etch and penetrate the passivation film of the photovoltaic device after sintering, and make a low-resistance contact with the p-type semiconductor. This is an effect that is difficult to achieve with conventional conductive pastes that do not contain aluminum. One of the reasons is that the conductive paste that does not contain aluminum powder cannot make a low-resistance electrical contact with the p-type semiconductor after penetrating the passivation film of the photovoltaic device, which ultimately affects the efficiency of the photovoltaic device.

[0145] The inventors have also found that selenium oxide is useful for lowering the softening point and melting temperature of the conductive paste and for improving its fluidity.

[0146] Furthermore, the n-type conductive paste composition in some embodiments of the present application does not contain the highly toxic elements thallium, chromium, and lead, and the toxicity of the entire conductive paste can be controlled within a low toxicity range.

[0147] Therefore, the bismuth-boron-selenium glass frit (containing Bi-B-Se oxide) in some embodiments of the present application can be used in place of the known lead-boron-selenium glass frit (containing Pb-Si-B oxide) in combination with a silver-aluminum paste to produce an n-type conductive paste composition that can penetrate the passivation film and make good electrical contact with the p-type semiconductor underneath the passivation film when manufacturing a photovoltaic device.

[0148] Method for producing second type of conductive paste composition Some embodiments of the present application provide a method for preparing a second conductive paste composition, which includes mixing the conductive component, the bismuth-boron-selenium glass frit and the aluminum simplex component according to the above-mentioned mixing ratio, dispersing them in a certain amount of organic medium, and forming a second conductive paste composition after uniform dispersion. The mixing ratio of the bismuth-boron-selenium glass frit, the conductive component and the aluminum simplex component needs to be adjusted to ensure that the sum of the weight percentages of the three components in the total solid matter of the conductive paste composition is 100%.

[0149] Application of the second type of conductive paste composition The conductive paste composition in some embodiments of the present application can be used in the manufacture of photovoltaic devices, such as solar cells. Illustratively, the conductive paste composition quickly etches the passivation film of the photovoltaic device during the sintering process, and ultimately penetrates the passivation film to make electrical contact with the p-type semiconductor of the photovoltaic device with low resistivity. The p-type semiconductor may be a p-type emitter preferably made from a silicon substrate.

[0150] Some embodiments of the present application provide a third type of photovoltaic device, which is an n-PERT solar cell (Passivated Emitter, Rear Totally Diffused), and uses a second type of conductive paste composition during manufacture. Other than that, the structure, materials, and manufacturing method are the same as those of the first type of photovoltaic device. The description of the first type of photovoltaic device in the present application is incorporated herein by reference.

[0151] Some embodiments of the present application provide a fourth type of photovoltaic device, which is a tunnel oxide passivated contact solar cell (Tunnel Oxide Passivated Contact, n-TOPCon), and uses a second type of conductive paste composition during manufacture. Other than that, the structure, materials, and manufacturing methods are similar to those of the first type of photovoltaic device. The description of the second type of photovoltaic device in the present application is incorporated herein by reference.

[0152] The technical solutions of the present application are further described below with reference to specific examples.

[0153] Examples 1-5 relate to lead-boron-selenium glass frits.

[0154] The contents of each component in the lead-boron-selenium glass frits of Examples 1 to 5 and the lead-boron-selenium glass frits of Comparative Examples 1 to 6 are shown in Tables 1 and 2. Each value in the table is a weight percentage (wt%). For example, 74.5 in Example 1 indicates that PbO in the example occupies 74.5 wt% of the total weight of the lead-boron-selenium glass frit in Example 1. The other components are the same. Quality inspection data of n-PERT solar cells manufactured from the lead-boron-selenium glass frits of Examples 1 to 5 and the lead-boron-selenium glass frits of Comparative Examples 1 to 6 are shown in Table 3.

[0155] [Table 1]

[0156] [Table 2]

[0157] A conductive paste composition is prepared using the lead-boron-selenium glass frit of each example and the glass frit of the comparative example, and an n-type solar cell is prepared using the conductive paste composition. The paste used on the front surface of the two types of n-type solar cells in the above examples may be the same. When the sum of the solid contents in the conductive paste is calculated as 100 wt%, the conductive paste composition contains 4.38% lead-boron-selenium glass frit, 94.52% conductive component (silver powder), and 1.1% aluminum simple component (aluminum powder). In some examples, the contents of the three types of components may not be limited to the above values.

[0158] [Table 3]

[0159] In the above table, the series resistance R s is the resistance r of the metal gate line as the front electrode mf , the contact resistance between the metal gate line and the front surface r cl , resistance of the front surface diffusion layer r t , base resistance r b , the contact resistance between the lower electrode and the semiconductor silicon r c2 , the resistance r of the top electrode metal gate line mb That is, R s =r mf +r cl +r t +r b +r c2 +r mb It is.

[0160] The conversion efficiency η is the ratio of the maximum power of the solar cell when irradiated to the total radiated power P 総 This refers to the percentage of I sc U oc FF / P 総 =U mp I mp / (A t P in ), and U mp and I mpare the voltage and current corresponding to the maximum output power point, respectively, and A t is the total area of ​​the solar cell, P in is the power of incident light per unit area. In actual testing, a Berger IV model efficiency tester is used to test the efficiency of the solar cell. The test method includes using a xenon arc lamp of the efficiency tester to simulate sunlight with an intensity of AM1.5 and irradiating it on the front of the solar cell, measuring the current and voltage values ​​at each point of the solar cell using a multi-point contact method, generating a current-voltage curve of the solar cell, and calculating the efficiency of the solar cell based on the current-voltage curve.

[0161] The fill factor (FF) is the ratio of the maximum power of a solar cell to the product of the open circuit voltage and the short circuit current, i.e., FF = I mp U mp / (I sc U oc ), wherein I sc U oc is the limiting output power of the solar cell, and I mp U mp is the maximum output power of the solar cell.

[0162] The manufacturing method of the lead-boron-selenium glass frit of the above examples and comparative examples includes the steps of mixing each component according to the compounding ratio shown in Table 1 and Table 2, then heat treating it in a crucible or melting furnace at a heat treatment temperature of 900 ° C to 1200 ° C, and continuing the heat treatment for 30 minutes after each component reaches a completely molten state, then quenching, crushing, sieving, and then D 50 and obtaining a powder having a diameter of 1.0 to 3.0 micrometers, i.e., lead-boron-selenium glass frit.

[0163] In the lead-boron-selenium glass frits of Examples 1 to 5 and Comparative Examples 1 to 6, components such as B2O3, SiO2, and Al2O3 are used to form a glass network system, metal components with low melting points such as SeO2, TeO2, Li2O, K2O, and Na2O are used to lower the Tg point (glass transition temperature) of the entire glass system, and PbO, Bi2O3, and ZnO are glass modifiers that modify the glass system and have a certain corrosiveness, and are used to etch and penetrate the passivation film of the photovoltaic device when sintering the conductive paste and the photovoltaic device, thereby making electrical contact with the P-type semiconductor of the photovoltaic device.

[0164] TeO2 was added to the lead-boron-selenium glass frit of the comparative example, and SeO2 was added to the lead-boron-selenium glass frit of the example. After testing the above comparative examples and examples, the inventors surprisingly found that after the lead-boron-selenium glass frits in the comparative examples and examples were prepared into n-type conductive paste compositions containing silver-aluminum paste and applied to the surface of the passivation film of a photovoltaic device, in the subsequent sintering process, TeO2 in the conductive paste of the comparative example oxidized the aluminum element in the silver-aluminum paste of the conductive paste to aluminum oxide, so that low-resistance electrical contact could not be made with the p-type semiconductor of the photovoltaic device, which reduced the efficiency of the photovoltaic device.

[0165] As shown in the Tg data in Table 3, the Tg points in each Example were all lower than those in the Comparative Example, which indicates that the Tg point can be lowered by using SeO2 instead of TeO2.

[0166] As shown in the series resistance data in Table 3, when the TeO2 content exceeds 1.3 wt%, the contact resistance increases significantly. This indicates that as the TeO2 content increases, the degree of oxidation of aluminum element increases, so the contact resistance increases. As the contact resistance increases, the fill factor and efficiency of the photovoltaic device also decrease.

[0167] Table 3 shows that the efficiency of the photovoltaic device decreases rapidly with increasing amount of TeO2. As can be seen from the data of Comparative Example 3, when the content of TeO2 is 1.3 wt%, the efficiency of the solar cell decreases to 8.83%, which cannot meet the efficiency requirements when the photovoltaic device is normally used. As can be seen from the data of Comparative Examples 4 to 6, with further increase in the content of TeO2, the efficiency of the solar cell decreases, even to below 5%. This shows that even a small amount of TeO2 can oxidize the aluminum element in the silver-aluminum paste, which has a significant effect on the efficiency of the photovoltaic device.

[0168] Table 3 also shows that the efficiency of the photovoltaic device does not change essentially with the increase in the amount of SeO2 added. As can be seen from the data of Examples 1 to 5 in Table 3, even if the content of SeO2 in the glass frit increases from 1.9% to 13.1%, the efficiency of the photovoltaic device does not fall below 21%, which can meet the efficiency requirements for photovoltaic devices in commercial applications. This indicates that even if the amount of SeO2 added is much higher than that of TeO2, it does not essentially oxidize the aluminum element in the silver-aluminum paste, thereby not affecting the contact resistance between the aluminum element and the P-type semiconductor of the photovoltaic device, and further not affecting the efficiency of the photovoltaic device.

[0169] Examples 6-9 relate to bismuth-boron-selenium glass frits.

[0170] Compared with Examples 1 to 5, the bismuth-boron-selenium glass frit of this embodiment uses bismuth oxide instead of lead oxide. In order to keep the efficiency of the photovoltaic device basically constant, the bismuth oxide and lead oxide should not be replaced in an equal ratio of 1:1, but should be adjusted according to the specific situation. The cation content of each composition is shown in Table 4.

[0171] [Table 4]

[0172] The bismuth-boron-selenium glass frit of each embodiment and the glass frit of the comparative example are used to prepare a conductive paste composition, and the conductive paste composition is used to prepare an n-type solar cell. The front paste of the two types of n-type solar cells mentioned in the above embodiments may be the same. When the sum of the solid content in the conductive paste composition is calculated as 100 wt%, the conductive paste composition contains 4.38% bismuth-boron-selenium glass frit, 94.52% conductive component (silver powder), and 1.1% aluminum simple component (aluminum powder).

[0173] [Table 5]

[0174] In Table 4, Bi2O3 is used instead of PbO, but the content of B2O3 and the content of Li2O are increased, and the content of Al2O3 and ZnO are decreased. In Table 3, K2O is not added, but K2O may be added as an alkali metal oxide in other examples. Comparative Example 7 shows that SeO2 is not added, and Examples 6 to 9 show that SeO2 is added with a gradually increasing content. Table 5 shows that the efficiency of the photovoltaic device has obvious advantages with the addition of SeO2. As can be seen from Table 5, after the conductive paste composition containing silver-aluminum paste is prepared using the above bismuth-boron-selenium glass frit and the conductive paste composition is formed on the surface of the passivation film of the photovoltaic device, the efficiency of the photovoltaic device is basically maintained between 21% and 22% during the sintering process, even if the content of SeO2 in the glass frit increases from 3.1 wt% to 12.4 wt%. This shows that in a lead-free system, even if the amount of SeO2 added reaches 12wt%, it does not oxidize the aluminum element in the silver-aluminum paste, and thus does not affect the resistivity of the aluminum element and the p-type semiconductor of the photovoltaic device, and does not affect the efficiency of the photovoltaic device. The efficiency test method of the photovoltaic device in this embodiment is the same as that in Example 1.

[0175] In addition, since the efficiency of the solar cell itself is limited, in the field of solar cells, if the efficiency fluctuation rate is 0.05%, the efficiency fluctuation is significant. As can be seen from Table 5, the negative control group does not contain SeO2, and the efficiency of the solar cell manufactured is 21.4%. The glass frit of Example 6 contains 3% SeO2, and the efficiency of the solar cell manufactured is improved by 0.3% compared to the negative control group. The glass frit of Example 7 contains 6% SeO2, and the efficiency of the solar cell manufactured is improved by 0.2% compared to the negative control group. The above data shows that the efficiency of the solar cell manufactured by adding a small amount of SeO2 is significant compared to the control example without adding SeO2, and that even if the amount of SeO2 added is high, the efficiency of the solar cell is not significantly reduced, and the efficiency of the solar cell can still be basically maintained between 21% and 22%.

[0176] As can be seen from the experimental data of Examples 1 to 9, there is no significant difference in the performance of the solar cells manufactured with the lead-boron-selenium glass frit and the bismuth-boron-selenium glass frit in terms of series resistance, efficiency, fill factor, etc., which indicates that the two types of glass frits can be interchanged when manufacturing solar cells. That is, the lead-boron-selenium glass frit and the bismuth-boron-selenium glass frit can be used not only to manufacture n-PERT solar cells, but also to manufacture n-TOPCon solar cells.

[0177] The above examples show that the present inventors have creatively invented lead-boron-selenium glass frit and bismuth-boron-selenium glass frit, and the two types of glass frits can be interchanged according to specific circumstances. After the glass frit is prepared into an n-type conductive paste composition containing silver-aluminum paste, the components therein do not excessively oxidize the aluminum element in the silver-aluminum paste during sintering, and therefore it can be used to manufacture photovoltaic devices with low resistivity.

[0178] The present application has been described in detail above. Although the principles and embodiments of the present application have been described in this specification using specific examples, the above description of the examples is merely intended to aid in the understanding of the method and gist of the present application, and those skilled in the art can modify the specific embodiments and scope of application in light of the concept of the present application. In other words, the contents of this specification should not be understood as limiting the present application. [Explanation of symbols]

[0179] 110 Semiconductor substrate 100 n-type crystalline silicon substrate (also called n-type lightly doped substrate) 101 Front p-type emitter (also called p-type semiconductor) 102 Back surface electric field (n + (also called highly doped semiconductors) 103 Front passivation film 104 Backside passivation film 105 Front silver aluminum paste 106 Backside metallization paste 107 Front conductive structure 108 Back conductive structure 210 Semiconductor substrate 200 n-type crystalline silicon substrate 201 Front p-type emitter 202a Tunnel passivation film 202b n + Polycrystalline Silicon Layer 203 Front passivation film 204 Backside passivation film 205 Front silver aluminum paste 206 Backside metallization paste 207 Front conductive structure 208 Back conductive structure

Claims

1. A conductive paste composition comprising: a lead-boron-selenium glass frit comprising 0.5 wt % to 10 wt % of the total solids of the conductive paste composition; A conductive component which is one or a mixture of a plurality of components selected from silver, a silver alloy, and a silver salt, and which occupies 87 wt % to 99 wt % of the total solid matter; An aluminum component that accounts for 0.5 wt % to 3 wt % of the total solids; an organic medium; Calculated based on the total weight of the dry weight of the lead-boron-selenium glass frit, the lead-boron-selenium glass frit contains at least 50 wt % to 85 wt % PbO, 2 wt % to 34 wt % B 2 O 3 and 0.1 wt% to 16 wt% SeO 2 Contains Conductive paste composition.

2. The lead-boron-selenium glass frit further contains 0.1 wt % to 25 wt % of an additive, calculated based on the total weight of the dry weight of the lead-boron-selenium glass frit, and the additive is PbF 2 , SiO 2 , Bi 2 O 3 , BiF 3 , AgO 2 , Ag 2 O, AgO, ZnO, MgO, CaO, Al 2 O 3 , Li 2 O, Na 2 O.K. 2 O, Rb 2 O, Ce 2 O and Fe 2 O 3 Any one or more selected from the group consisting of: The conductive paste composition according to claim 1 .

3. Based on the total weight of the dry weight of the lead-boron-selenium glass frit, the SeO 2 The content is 2 wt% to 10 wt%. The conductive paste composition according to claim 1 .

4. The lead-boron-selenium glass frit contains 1.2 wt % or less TeO, calculated based on the total dry weight of the lead-boron-selenium glass frit. 2 or does not contain any form of elemental tellurium; The conductive paste composition according to claim 1 .

5. The lead-boron-selenium oxide contained in the lead-boron-selenium glass frit is in a completely amorphous state, or the lead-boron-selenium oxide contained in the lead-boron-selenium glass frit is partly in an amorphous state and partly in a crystalline state; The conductive paste composition according to claim 1 .

6. A use of the conductive paste composition according to claim 1 in an n-type crystalline silicon solar cell, wherein the conductive paste composition etches through the passivation film of the n-type crystalline silicon solar cell to form a conductive structure that makes an electrical connection with the p-type doped emitter of the n-type crystalline silicon solar cell. Use of the conductive paste composition in an n-type crystalline silicon solar cell.

7. Providing a semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and a passivation film deposited on a surface of the p-type doped emitter; Applying the conductive paste composition according to claim 1 in a pattern on at least a portion of the surface of the passivation film; and sintering the semiconductor substrate and the conductive paste composition, the conductive paste composition etching through the passivation film during the sintering process to form a conductive structure making electrical connection with the p-type doped emitter, thereby obtaining an n-type crystalline silicon solar cell electrode. A method for manufacturing an n-type crystalline silicon solar cell electrode.

8. A semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and at least one layer of a passivation film deposited on a surface of the p-type doped emitter; a conductive structure formed of the conductive paste composition of claim 1, the conductive structure penetrating at least a portion of the passivation film and electrically connecting with the p-type doped emitter. n-type crystalline silicon solar cell electrode.

9. n-PERT solar cell electrode or n-TOPCon solar cell electrode; The n-type crystalline silicon solar cell electrode according to claim 8 .

10. A conductive paste composition comprising: a bismuth-boron-selenium glass frit comprising 0.5 wt % to 10 wt % of the total solids of the conductive paste composition; A conductive component which is one or a mixture of a plurality of components selected from silver, a silver alloy, and a silver salt, and which occupies 87 wt % to 99 wt % of the total solid matter; An aluminum component that accounts for 0.5 wt % to 3 wt % of the total solids; an organic medium; The bismuth-boron-selenium glass frit contains at least 50 wt % to 90 wt % Bi, calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit. 2 O 3 , 2 wt% to 35 wt% B 2 O 3 and 0.1 wt% to 15 wt% SeO 2 Contains Conductive paste composition.

11. When calculated based on the total weight of the bismuth-boron-selenium glass frit, the SeO 2 The content is 2 wt% to 12 wt%. The conductive paste composition according to claim 10.

12. The bismuth-boron-selenium glass frit contains 0.1 wt % to 5 wt % Li, calculated based on the total dry weight of the bismuth-boron-selenium glass frit. 2 and / or Calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit, the bismuth-boron-selenium glass frit contains 0.1 wt % to 5 wt % Na 2 O, and / or the bismuth-boron-selenium glass frit further contains 0.1 wt % to 20 wt % ZnO, calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit. The conductive paste composition according to claim 10.

13. The bismuth-boron-selenium glass frit further contains 0.1 wt % to 25 wt % of an additive, calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit, and the additive is SiO 2 , BiF 3 , AgO 2 , Ag 2 O, AgO, ZnO, MgO, CaO, Al 2 O 3 , Li 2 O, Na 2 O.K. 2 O, Rb 2 O, Ce 2 O and Fe 2 O 3 Any one or more selected from the group consisting of: The conductive paste composition according to claim 12.

14. The bismuth-boron-selenium glass frit contains 1.2 wt % or less TeO, calculated based on the total weight of the dry weight of the bismuth-boron-selenium glass frit. 2 or does not contain any form of elemental tellurium; The conductive paste composition according to claim 10.

15. The bismuth-boron-selenium oxide contained in the bismuth-boron-selenium glass frit is in a completely amorphous state, or the bismuth-boron-selenium oxide contained in the bismuth-boron-selenium glass frit is partially in an amorphous state and partially in a crystalline state. The conductive paste composition according to claim 10.

16. 11. The use of the conductive paste composition according to claim 10 in an n-type crystalline silicon solar cell, wherein the conductive paste composition etches through the passivation film of the n-type crystalline silicon solar cell to form a conductive structure that makes an electrical connection with the p-type doped emitter of the n-type crystalline silicon solar cell. Use of the conductive paste composition in an n-type crystalline silicon solar cell.

17. Providing a semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and at least one passivation film deposited on a surface of the p-type doped emitter; Applying the conductive paste composition according to claim 10 in a pattern on at least a portion of the surface of the passivation film; and sintering the semiconductor substrate and the conductive paste composition, the conductive paste composition etching through the passivation film during the sintering process to form a conductive structure making electrical connection with the p-type doped emitter, thereby obtaining an n-type crystalline silicon solar cell electrode. A method for manufacturing an n-type crystalline silicon solar cell electrode.

18. A semiconductor substrate having an n-type crystalline silicon substrate, a p-type doped emitter provided on a surface of the n-type crystalline silicon substrate, and at least one layer of a passivation film deposited on a surface of the p-type doped emitter; a conductive structure formed of the conductive paste composition of claim 10, the conductive structure penetrating at least a portion of the passivation film and electrically connecting with the p-type doped emitter. n-type crystalline silicon solar cell electrode.

19. n-PERT solar cell electrode or n-TOPCon solar cell electrode; 20. The n-type crystalline silicon solar cell electrode according to claim 18.

Citation Information

Patent Citations

  • Crystalline oxides, preparation thereof and conductive pastes containing the same

    CN107089798A

  • Glass powder composition, conductive silver paste containing glass powder composition, and preparation method of conductive silver paste

    CN107746184A

  • Electronic glass powder for positive silver paste of solar crystalline silicon battery and preparation method thereof

    CN110407467A

  • Silver-aluminum paste for P + electrode of solar cell and solar cell

    CN113409986A

  • Conductive paste for solar cell element and method of manufacturing solar cell element using the same

    JP2007281023A